THE EFFECT OF HEATING ON PHYSICOCHEMICAL CHARACTERISTICS OF RICE BRAND OIL - S. Dewi Indrasari; Sutrisno Koswara; Deddy Muchtadi; L. Mulyati Nagara (Indonesian Agency for Agricultural Research and Development, 2001)
Rice bran oil has a potential in lowering blood cholesterol. The oil content extracted from rice bran isa influenced by several factors such as raw material and processing method. This research was conducted to study the effect of heating on the physicochemical characteristics of rice bran oil. The study was carried out at the Food Technology and Nutrition Laboratory and Biotechnological Science Laboratory of the Inter University Center, Bogor Agricultural University, from February to MAy 1997. Bran used was from IR64 rice variety obtained from a local milling rice in Tambak Dahan, Binong-Subang, West Java. Rice bran was subjected to different period of heating (0, 15 and 30 minutes) at 121oC by using an autoclave, then the oil was extraxted by using hexane solvent followed by standard processing at room temperature (28-30oC) and 40oC for two hours. The parameters observed were oil content and its quality such as saponification, iodine, acid, peroxide, tiobarbituric acid, and triglyceric acid values as well as oil color. The results showed that oil extracted from rice bran was high, ranging from 9.65 to 11.02%. Heating (sterilizing) of the rice bran for 15 and 30 minutes at 120oC proir to extraction increased the oil content. The Quality of rice bran oil extracted met the standard of AOAC.